Risk factors and epidemiology of Clostridium difficile infection in hematopoietic stem cell transplant recipients during the peritransplant period. Issue 1 (February 2017) - Aldrete, Sol del Mar; Kraft, Colleen S.; Magee, Matthew J.; Chan, Austin; Hutcherson, Don; Langston, Amelia A.; Greenwell, Brian I.; Burd, Eileen M.; Friedman‐Moraco, Rachel
Abstract: Background: Hematopoietic stem cell transplant (HSCT) recipients represent a high‐risk group for developing Clostridium difficile (CD) infection (CDI). We aimed to identify specific risk factors for CDI in an HSCT patient population during the peritransplant period. Methods: We performed a case–control study within a cohort of HSCT patients who received a transplant from November 2010 to March 2013. Cases had a clinical presentation compatible with CDI and a positive stool sample Xpert ® C. difficile test. Controls were CDI negative and matched on age, gender, and transplant type. Peritransplant period was defined as −30 days or time of stem cell mobilization maneuver to 30 days post transplant in autologous SCT or 90 days post transplant in allogeneic SCT. Results: Of 781 HSCTs performed during the study period, 650 (83.2%) had a stool sample submitted for CD testing. Eight‐six (13.2%) cases with CDI were identified. Most of the cases were diagnosed within a week after transplantation (median of 5 days). In adjusted analysis, prior hospitalization (odds ratio [OR]: 2.01, 95% confidence interval [CI] 1.2‐3.36), prior cephalosporin administration (OR 2.72, 95% CI: 1.54‐4.83), and prior chemotherapy (OR: 3.26, 95% CI: 1.92‐5.5) were significantly associated with CDI. Conclusions: Hospitalization, and prior antibiotic and chemotherapy use are risk factors that are not easily modifiable, which emphasizes the need to start investigating preventive or prophylactic strategies in this high‐risk population.